Formalising Meaning: a History of Programming Language Semantics - Troy Astarte (2019)
The emergence of high-level programming languages in the 1950s brought a series ofchallenges to the burgeoning computing community. Many of these centred aroundthe difficulty of determining precisely the meaning of programming languages. Thiswas a key issue for both those writing translators for languages and those writingprograms in these languages. People in the computing and mathematics worldsattempted to address these challenges by creating a variety of ways to describe thesemantics of high-level languages (the issue of defining syntax was more quicklyresolved).The history of the development of formal semantic description techniques is explored, with a particular focus on two centres of research: the IBM Laboratory inVienna, and the Programming Research Group in Oxford. The stories of these twothreads of development create interesting contrasts and similarities and discussingthem—as well as the previous works that motivated them and the subsequent workinspired by them—can tell us much about programming languages and formal computing today, as well as the culture and context of computing in the 1960s and 1970s.This work takes both a historical and technical approach. Looking at historicaldevelopments, considering the people involved in research, their motivations, thesituations in which they worked, and how they interacted informs understanding oftheir technical outputs. Exploring the technical side, however, also helps uncoveradditional historical angles, such as interactions and influences both positive andnegative.